Sero – epidemiology of brucellosis in people and their livestock: A linked human – animal cross-sectional study in a pastoralist community in Kenya - Muema, Josphat; Oboge, Harriet; Mutono, Nyamai; Makori, Anita; Oyugi, Julius; Bukania, Zipporah; Njuguna, Joseph; Jost, Christine; Ogoti, Brian; Omulo, Sylvia; Thumbi, S. M. (Frontiers in Veterinary Science, 2022)
Background: Brucellosis is associated with massive livestock production losses and human morbidity worldwide. Efforts to control brucellosis among pastoralist communities are limited by scarce data on the prevalence and risk factors for exposure despite the high human-animal interactions in these communities. This study simultaneously assessed the seroprevalence of brucellosis and associated factors of exposure among pastoralists and their livestock in same households. Methods: We conducted a cross-sectional study in pastoralist communities in Marsabit County – Kenya. A total of 1,074 women and 225 children participated and provided blood samples. Blood was also drawn from 1,876 goats, 322 sheep and 189 camels. Blood samples were collected to be screened for the presence of anti-Brucella IgG antibodies using indirect IgG Enzyme-Linked Immunosorbent Assay (ELISA) kits. Further, Individual, household and herd-level epidemiological information were captured using a structured questionnaire. Group differences were compared using the Pearson’s Chi-square test, and p-values <0.05 considered statistically significant. Generalized mixed-effects multivariable logistic human and animal models using administrative ward as the random effect was used to determine variables correlated to the outcome. Results: Household-level seropositivity was 12.7% (95% CI: 10.7 – 14.8). The individual human seroprevalence was 10.8% (9.1 – 12.6) with higher seroprevalence among women than children ( 12.4% vs 3.1%, p < 0.001). Herd-level seroprevalence was 26.1% (23.7 – 28.7) and 19.2% (17.6 – 20.8) among individual animals. Goats had the highest seroprevalence 23.1% (21.2 – 25.1), followed by sheep 6.8% (4.3 – 10.2) and camels 1.1% (0.1 – 3.8). Goats and sheep had a higher risk of exposure OR = 3.8 (95% CI 2.4–6.7, p<0.001) and 2.8 (1.2–5.6, p<0.007), respectively relative to camels. Human and animal seroprevalence were significantly associated (OR = 1.8, [95%CI: 1.23 – 2.58], p = 0.002). Herd seroprevalence varied by household head education (OR=2.45, [1.67–3.61,p<0.001]) and herd size (1.01, [1.00–1.01], p<0.001). Conclusions: The current study showed evidence that brucellosis is endemic in this pastoralist setting and there is a significant association between animal and human brucellosis seropositivity at household level representing a potential occupational risk. Public health sensitization and sustained human and animal brucellosis screening are required.